Análise de marcadores culturais no par de obras Relato de um certo oriente e The tree of the seventh heaven - Frisene, Patricia Dias Reis [UNESP]; Camargo, Diva Cardoso de [UNESP] (My University, 2010)
This paper presents some results of a study on culturally marked terms in a corpus composed by the Brazilian novel Relato de um certo oriente (1989), by Milton Hatoum, and its translation into English The tree of the seventh heaven, by Ellen Watson. For the analysis of culturally marked terms, we followed the interdisciplinary approach proposed by Camargo (2005, 2007) involving corpus-based translation studies (BAKER, 1993, 1995, 1996, 2000), and the investigations of cultural domains (NIDA, 1945; AUBERT, 1981, 2006). The methodology adopted in the present research required the software WordSmith Tools (SCOTT, 2007), which provides the necessary resources for the collection of data in a corpus of translated texts. The software tool called WordList was used for the selection of the most frequent words in the texts and also for the identification of the culturally marked terms. For the analysis of the culturally marked terms in both texts we used the software tool Concord. The results revealed that most of the culturally marked terms are inserted in the ecological domain, and the other terms are distributed in the domains of material, social and ideological culture, which reflects the theme of the book.

O presente artigo tem por objetivo analisar a tradução para o inglês de marcadores culturais na obra Relato de um certo oriente, de Milton Hatoum. Para a realização da pesquisa, apoiamo-nos na abordagem interdisciplinar proposta por Camargo (2005, 2007) envolvendo os estudos da tradução baseados em corpus (BAKER, 1993, 1995, 1996, 2000) e nos trabalhos sobre domínios culturais (NIDA, 1945; AUBERT, 1981, 2006). A metodologia adotada nesta investigação utiliza o programa WordSmith Tools (SCOTT, 2007), que oferece ferramentas necessárias para o levantamento de dados em corpus de textos traduzidos. Por meio da ferramenta WordList, realizamos o levantamento das palavras de maior frequência no corpus e a seleção dos marcadores culturais. Depois, cada marcador foi examinado dentro de seu cotexto, com o auxílio da ferramenta Concord. Os resultados obtidos revelaram que a maioria dos marcadores culturais mostra-se inserido no domínio ecológico, e os outros marcadores nos domínios da cultura material, social e ideológica, o que espelha a temática da obra.
Analysis of culturally marked terms in Relato de um certo Oriente and The Tree of the Seventh Heaven
Keywords: Literatura Brasileira; Tradução; Milton Hatoum; Brazilian Literature; Translation; Milton Hatoum